Impact of Microfinance Banks on the Performance of Micro, Small and Medium Enterprises (MSMEs): A Study of Federal Capital Territory, Abuja, Nigeria - Song, Muru Bitrus; Jimaza, Michael; Okoroafor, O. K. David (ORGANIZE: Journal of Economics, Management and Finance, 2025)
The study examined the impact of microfinancing on the performance of micro, small and medium enterprises in Federal Capital Territory, Abuja, Nigeria. Four-hundred MSMEs owners were sampled using the Yamane (1967) method in all the six Area Councils of Abuja. Also, the descriptive statistics which include frequency, percentage and cumulative percentage were used in analyzing the socio-economic characteristics of the respondents; while, the logit regression was used to analyze the formulated objectives of the study. The logit regression estimates showed that loans from microfinance banks, economical age active, loan from family members and other sources were explicitly significant and directly impact the MSMEs; while, loans from commercial banks was also significant and indirectly impact it. These imply that MSMEs that have access to loan from microfinance banks is 20.0% likely to expand their production capacity than non-customer. The study concluded that MSMEs operations that have access to credit from microfinance banks experience growth in their business performance; while reverse is the case for non-customers. The study recommended that the apex bank within the country should ensure that the micro-finance banks comply with the core values of its operations that concerns with promoting rural development through financial inclusion and financial literacy, deposit mobilization, and credit delivery to finance micro-enterprises.